2021
DOI: 10.3390/plants10122597
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Computational Analysis of the Sulfotransferase (SOT) Gene Family in Potato (Solanum tuberosum): Insights into Sulfur Adjustment for Proper Development and Stimuli Responses

Abstract: Various kinds of primary metabolisms in plants are modulated through sulfate metabolism, and sulfotransferases (SOTs), which are engaged in sulfur metabolism, catalyze sulfonation reactions. In this study, a genome-wide approach was utilized for the recognition and characterization of SOT family genes in the significant nutritional crop potato (Solanum tuberosum L.). Twenty-nine putative StSOT genes were identified in the potato genome and were mapped onto the nine S. tuberosum chromosomes. The protein motifs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…The PgZFP gene family was categorized into 17 subcategories at Level 2 and revealed to have 53 types of cis-regulatory elements responsive to multiple biological processes, suggesting that during the evolutionary process, changes have substantially occurred in the structure and upstream regions of PgZFP genes and these changes have affected their functional diversity 36 38 . The functional diversity of the gene family is larger than those of PgbHLH 49 , PgNAC 50 , and PgGRAS 51 gene families in ginseng that were categorized into 11, 8, and 15 subcategories, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PgZFP gene family was categorized into 17 subcategories at Level 2 and revealed to have 53 types of cis-regulatory elements responsive to multiple biological processes, suggesting that during the evolutionary process, changes have substantially occurred in the structure and upstream regions of PgZFP genes and these changes have affected their functional diversity 36 38 . The functional diversity of the gene family is larger than those of PgbHLH 49 , PgNAC 50 , and PgGRAS 51 gene families in ginseng that were categorized into 11, 8, and 15 subcategories, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The transcripts with complete CDS were used for Ka/Ks calculation using the KaKs_Calculator 35 . The time of the gene duplication and divergence was estimated by T = Ks/2λ × 10 −6 , where Ks is synonymous nucleotide substitution rate and λ is the number of substitutions per synonymous site per generation, for which λ = 6.5 × 10 −9 was used 36 38 .…”
Section: Methodsmentioning
confidence: 99%
“…This suggested that the FAR1/FHY3 genes might have been involved in the responses to heat shock rather than the cold stress, despite of their lagged response under high-temperature stress. In conclusion, FAR1/FHY3 genes in E. grandis showed a diverse expression in response to abiotic stresses, indicating that they are involved in different cellular processes and cell signaling (Faraji et al, 2021 ; Heidari et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that evolutionary pressures can extend the members of the gene family ( Abdullah et al, 2021 ; Musavizadeh et al, 2021 ). Moreover, mutations in coding sites and promoter regions can affect the function of members of the gene family ( Faraji et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%